2012
DOI: 10.1093/eurheartj/ehs309
|View full text |Cite
|
Sign up to set email alerts
|

Impact of thrombus aspiration during primary percutaneous coronary intervention on mortality in ST-segment elevation myocardial infarction

Abstract: This study of real-world, unselected STEMI patients demonstrates that thrombus aspiration during PPCI is associated with a significant reduction in mortality, especially in those with a short total ischaemic time. These findings support the use of thrombectomy during PPCI in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 28 publications
5
22
0
Order By: Relevance
“…Similar results were reported by Kilic et al [21]. On the contrary, in two large real world registries, thrombus aspiration was associated with long-term clinical benefit [22,23]. Data from randomized trials are even more inconclusive and meta-analyses are not able to shed light on the real efficacy of thrombectomy.…”
Section: Discussionsupporting
confidence: 72%
“…Similar results were reported by Kilic et al [21]. On the contrary, in two large real world registries, thrombus aspiration was associated with long-term clinical benefit [22,23]. Data from randomized trials are even more inconclusive and meta-analyses are not able to shed light on the real efficacy of thrombectomy.…”
Section: Discussionsupporting
confidence: 72%
“…16 All other clinical and interventional parameters have been described in our previous publications. 20,21 Statistics Continuous variables are presented as median and interquartile range (IQR: 25 th -75 th ). Categorical variables were compared by the χ 2 test, and continuous variables by the independent t-test or Mann-Whitney U test as appropriate.…”
Section: Clinical Data and Shock Indexmentioning
confidence: 99%
“…recently analyzed prospective data for 2,567 consecutive STEMI patients treated with p-PCI and reported that thrombectomy was associated with significant reductions in in-hospital mortality (OR 0.51, 95% CI 0.29-0.93, p = 0.027) and long-term mortality (OR 0.69, 95% CI 0.48-0.96, p = 0.028) during a mean follow-up of 9.9±3.8 months 72) . Based on these findings, if not anatomically contraindicated, adjunctive manual thrombectomy devices should be widely and routinely used in STEMI patients undergoing p-PCI.…”
Section: Mechanisms Of Coronary Thrombus Formationmentioning
confidence: 99%